Application of Fuzzy Logic in Air Conditioner Temperature Control in Rooms with Partitions in Boarding Houses - Ihda Rahmadaniar; Muhammad Karim Bachtiar; Ramma Dwi Rachmat; Danang Mukti Darmawan; Fiqri Nurfadillah; Nanda Octavia (Batrisya Education, 2024)
This research investigates the application of fuzzy logic with the Mamdani method to regulate room temperature using an air conditioner (AC) in a boarding house environment with a partition at Bogor City, Indonesia. By considering variables such as room size, external temperature (weather), and air conditioner specifications, this research aims to achieve a balance between occupant comfort and energy efficiency. The optimal temperature for each room in the boarding house will be determined through fuzzy logic calculations. This research aims to open up new potentials in intelligent and sustainable temperature regulation in a boarding house or similar environment. This research method uses fuzzy logic for room temperature control using Matlab software.